Electromagnetic analysis for the side-coupled cavity-type interaction structure for the linear accelerators. Issue 4 (3rd March 2020) - Tripathi, Prabhakar; Kumar, Arjun; Dwivedi, Smrity; Jain, P. K.
Abstract : The side-coupled cavity (SCC) structure is widely used in Linac, and also finds its application in the high-power microwave tubes. The SCC structure operating under the slow-wave regime, for the π /2 mode in transverse magnetic mode operation, has been electromagnetically analyzed using field-matching technique for the dispersion and interaction impedance characteristics. Furthermore, the effect of different structural parameters on the dispersion and interaction characteristics has been studied. To validate the developed dispersion and interaction relation, the SCC is simulated using commercially available electromagnetic simulation tools. The results obtained through the developed analytical expression are compared with the simulated results, and it is found to be in agreement within 3%. This analysis will help the design engineer to select the approximate accurate parameters before performing the simulation or experimental design. Also, it helps to develop a better understanding about the SCC's behavior with respect to structural parameter before the simulation.